Pagos por Servicios Ambientales para sistemas silvopastoriles en Colombia - Díaz, Manuel Francisco; Enciso, Karen; Triana Ángel, Natalia; Muriel, Juliana; Burkart, Stefan (International Center for Tropical Agriculture, 2019)
This study aims to combine theory on payments for ecosystem services (PES) with examples from practice, examining the meeting points, barriers and opportunities that have occured and can be developed by applying PES schemes for the establishment of silvopastoral systems in Colombia. This research is based on a framework in which political, economic, institutional, environmental and contextual factors are examined in order to generate a critical diagnosis of these elements in relation to the dynamics generated or that can be build from the implementation of such schemes. The implementation of PES in the country is analyzed and recommendations are provided on their effectiveness in order to integrate the opportunities and overcome the described challenges.